Spectral study of the diffuse synchrotron source in the galaxy cluster Abell 523. Issue 3 (4th February 2022) - Vacca, Valentina; Shimwell, Timothy; Perley, Richard A; Govoni, Federica; Murgia, Matteo; Feretti, Luigina; Giovannini, Gabriele; Loi, Francesca; Carretti, Ettore; Cova, Filippo; Gastaldello, Fabio; Girardi, Marisa; et al.
ABSTRACT: The galaxy cluster Abell 523 (A523) hosts an extended diffuse synchrotron source historically classified as a radio halo. Its radio power at 1.4 GHz makes it one of the most significant outliers in the scaling relations between observables derived from multiwavelength observations of galaxy clusters: it has a morphology that is different and offset from the thermal gas, and it has polarized emission at 1.4 GHz typically difficult to observe for this class of sources. A magnetic field fluctuating on large spatial scales (∼1 Mpc) can explain these peculiarities but the formation mechanism for this source is not yet completely clear. To investigate its formation mechanism, we present new observations obtained with the LOw Frequency ARray at 120–168 MHz and the Jansky Very Large Array at 1–2 GHz, which allow us to study the spectral index distribution of this source. According to our data the source is observed to be more extended at 144 MHz than previously inferred at 1.4 GHz, with a total size of about 1.8 Mpc and a flux density S_144 MHz=(1.52± 0.31) Jy. The spectral index distribution of the source is patchy with an average spectral index α ∼ 1.2 between 144 MHz and 1.410 GHz, while an integrated spectral index α 2.1 has been obtained between 1.410 and 1.782 GHz. A previously unseen patch of steep spectrum emission is clearly detected at 144 MHz in the south of the cluster. Overall, our findings suggest that we are observing an overlapping of different structures, powered by the turbulence associated with the primary and a possible secondary merger.